Determinants of Discipline of Micro, Small and Medium Enterprises Tax Bearers: Determinan Kedisiplinan Penanggung Pajak Usaha Mikro Kecil dan Menengah - Sabaruddin, Sabaruddin (Journal of Accounting Science, 2022)
This study aims to analyze how much influence awareness, understanding, tax sanctions, and income levels have on the discipline of small, micro, and medium enterprises (MSME) to bearers. The theory that underlies this research is the theory of planned behavior (TPB) which is related to the discipline of the tax bearer. Behavioral theory explains behavior change caused by several things. The population used in this study is MSME taxpayers registered with PD Pasar Jaya Jakarta, with a sample of 234 MSMEs. The analytical method used is multiple linear regression. The result of the independent test on the variable that taxpayer awareness has a negative and insignificant effect on the discipline of MSME tax bearers. However, the understanding of taxation has a positive and significant effect on MSME discipline. Likewise, tax sanction and the income level of the tax bearer has a positive and significant effect on MSME tax discipline. Meanwhile simultaneously testing the effect of awareness, understanding of taxation, tax sanctions, and income level a significant effect on MSME tax discipline. The implication of this research is that the discipline of the tax bearer can increase with high awareness and understanding of tax provisions.